Peran Komitmen Organisasi sebagai Mediasi pada Pengaruh Talent Management terhadap Employee Retention - Muhamad Ekhsan; Dita Manisha Ratman Sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of the study is to test the effect between talent management on employee retention mediated by the organization's commitment. The study is deductive approaches and quantitative methods. The quantitative study uses 29 structured questionnaire items distributed to 80 employees in PT. Melu Bangun Wiweka (MBW) by using an probability sampling technique. As many as 80 surveys can be collected and used. And the analysis uses a software modelling SmartPLS 3.0. Discovery in this study has had a positive and significant impact between talent management on employee retention, talent management on organization’s commitment, and organization’s commitment on employee retention. To further mediation regarding the role of mediation the organization's commitment between variable talent management and employee retention shown by model boostrapping by using SmartPLS and findings, reveals that of the three hypothesis roles of organization’s commitment mediation there are significantly effects between variables and manage between those talent management variables and employee retention. Therefore, the company has set the stage for improving the talent managemen and organization’s commitment to increase of employee retention.